PENGELOLAAN SUMBER DAYA ALAM DAN LINGKUNGAN BERBASIS PENGETAHUAN DAN KEARIFAN LOKAL (LOCAL WISDOM ) DI KALIMANTAN - Said Fadhil (Jurnal Borneo Administrator, 2007)
Improper management of natural resources all this time has caused bad impact towards human beings, such as floods, landslide, forest fire, air contamination and  other concerning condition. One of the triggers of these impacts is that management of natural resources done by the government has been conducted without involving the people around the resources itself. This article will portray the practices of local wisdom on how  people in Kalimantan manage the natural resources. The identification of the local wisdom is expected to stimulate the government to change the paradigm of natural resources management by using a continuing development concept with regard to continuity, balance and preservation principles supported by applying traditional knowledge and wisdom of local society.  Key Word: Sumber Daya Alam, Kearifan Lokal